Lack of cystic fibrosis transmembrane conductance regulator disrupts fetal airway development in pigs. (June 2018) - Meyerholz, David; Stoltz, David; Gansemer, Nick; Ernst, Sarah; Cook, Daniel; Strub, Matthew; LeClair, Erica; Barker, Carrie; Adam, Ryan; Leidinger, Mariah; Gibson-Corley, Katherine; Karp, Philip; et al.
Loss of cystic fibrosis transmembrane conductance regulator (CFTR) function causes cystic fibrosis (CF), predisposing the lungs to chronic infection and inflammation. In young infants with CF, structural airway defects are increasingly recognized before the onset of significant lung disease, which suggests a developmental origin and a possible role in lung disease pathogenesis. The role(s) of CFTR in lung development is unclear and developmental studies in humans with CF are not feasible. Young CF pigs have structural airway changes and develop spontaneous postnatal lung disease similar to humans; therefore, we studied lung development in the pig model (non-CF and CF). CF trachea and proximal airways had structural lesions detectable as early as pseudoglandular development. At this early developmental stage, budding CF airways had smaller, hypo-distended lumens compared to non-CF airways. Non-CF lung explants exhibited airway lumen distension in response to forskolin/IBMX as well as to fibroblast growth factor (FGF)-10, consistent with CFTR-dependent anion transport/secretion, but this was lacking in CF airways. We studied primary pig airway epithelial cell cultures and found that FGF10 increased cellular proliferation (non-CF and CF) and CFTR expression/function (in non-CF only). In pseudoglandular stage lung tissue, CFTR protein was exclusively localized to the leading edges of budding airways in non-CF (but not CF) lungs. This discreet microanatomic localization of CFTR is consistent with the site, during branching morphogenesis, where airway epithelia are responsive to FGF10 regulation. In summary, our results suggest that the CF proximal airway defects originate during branching morphogenesis and that the lack of CFTR-dependent anion transport/liquid secretion likely contributes to these hypo-distended airways.